2017
DOI: 10.1002/ece3.3304
|View full text |Cite
|
Sign up to set email alerts
|

Timing is everything: Fishing‐season placement may represent the most important angling‐induced evolutionary pressure on Atlantic salmon populations

Abstract: Fisheries‐induced evolution can change the trajectory of wild fish populations by selectively targeting certain phenotypes. For important fish species like Atlantic salmon, this could have large implications for their conservation and management. Most salmon rivers are managed by specifying an angling season of predetermined length based on population demography, which is typically established from catch statistics. Given the circularity of using catch statistics to estimate demographic parameters, it may be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…Those studies found that the wild type dominated completely among salmon that returned as 1SW fish while among 2SW fish, hybrids and domesticated type dominated. In the salmon population inhabiting the river Etne however, the majority of salmon returned after 2 years in the sea (Harvey, Tang, Wennevik, Skaala, & Glover, ). As a result, we observed that the wild type tended to be older than hybrids and domesticated types at return to spawn, albeit with sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies found that the wild type dominated completely among salmon that returned as 1SW fish while among 2SW fish, hybrids and domesticated type dominated. In the salmon population inhabiting the river Etne however, the majority of salmon returned after 2 years in the sea (Harvey, Tang, Wennevik, Skaala, & Glover, ). As a result, we observed that the wild type tended to be older than hybrids and domesticated types at return to spawn, albeit with sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…adequate water discharge). This could result in a mismatch be tween sampling and the effective spawning population (Harvey et al 2017). It has also been shown that the angling catch efficiency is quickly reduced after river entry (Harvey et al 2017), suggesting that variation in time of river entry (Erkinaro et al 2010, Svenning et al 2017) may cause different catch probabilities between wild and escaped salmon.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in a mismatch be tween sampling and the effective spawning population (Harvey et al 2017). It has also been shown that the angling catch efficiency is quickly reduced after river entry (Harvey et al 2017), suggesting that variation in time of river entry (Erkinaro et al 2010, Svenning et al 2017) may cause different catch probabilities between wild and escaped salmon. Furthermore, differences within the river in the distribution of escaped and wild salmon and variations in spatial CPUE during fishing may further underestimate or overestimate the proportion of escaped farmed salmon in the spawning populations (Moe et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the few cases where individuals shared an identical genetic profile to another fish, they were genotyped for a further five microsatellites to provide unambiguous individual identification. For full details regarding this procedure the reader is referred to previous work 59 , 60 .…”
Section: Methodsmentioning
confidence: 99%